PENGARUH KESADARAN MEREK DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ASUS DI KOTA SURABAYA - Permana, Moh Haris Indra; Maruta, IGN Anom; Novaria, Rachmawati (Jurnal Dinamika Administrasi Bisnis, 2015)
Perception of a product that is good and positive from consumers can be built through the brand. Manufacturers should be able to build brand their products as best as possible so that consumers can be loyal to a product that has been marketed as a strong brand will be able to change consumer behavior. The aim of this study is to analyze and determine the effect of brand awareness and perception of the quality of the Asus laptop purchase decision in Hitech - Mall Surabaya. The aim of this study is to analyze and determine the effect of brand awareness and perception of the quality of the Asus laptop purchase decision in Hitech - Mall Surabaya. The target population of this research is in the Hitech-Mall Surabaya with Laptops ASUS and samples of the population in this study were 100 Correspondent of the Asus laptops in Hitech-Mall Surabaya, while the method of sampling was done by using a non-probability sampling by means purposive sampling multiple regression Analysis. Results from this study showed that variables Brand Awareness and Quality Perception partially significant effect on purchase decision. It is known from tcount Brand Awareness by 4054 greater than ttable (1.9847), so the research hypothesis which says "no brand awareness influence on purchasing decisions Asus Laptop in Surabaya", can be declared acceptable. And tcount Quality Perception by 8909 greater than ttable (1.9847). so the research hypothesis which says "no influence on purchasing decisions perceived quality Laptop Asus in Surabaya", can be declared acceptable. Keywords: Brand Awareness, Perceived Quality and Purchase Decision